Adjunctive dexamethasone for the treatment of HIV-infected adults with tuberculous meningitis (ACT HIV): Study protocol for a randomised controlled trial - Donovan, J; Hoan Phu, N; Thi Hoang Mai, N; Tien Dung, L; Imran, D; Burhan, E; Hong Bao Ngoc, L; Duc Bang, N; Chau Giang, D; Thi Minh Ha, D; Day, J; Thi Phuong Thao, L; et al. (F1000Research, 2018)
Background: Tuberculous meningitis (TBM) is the most severe form of tuberculosis. Co-infection with HIV increases the risk of developing TBM, complicates treatment, and substantially worsens outcome. Whether corticosteroids confer a survival benefit in HIV-infected patients with TBM remains uncertain. Hepatitis is the most common drug-induced serious adverse event associated with anti-tuberculosis treatment, occurring in 20% of HIV-infected patients. The suggested concentration thresholds for stopping anti-tuberculosis drugs are not evidence-based. This study aims to determine whether dexamethasone is a safe and effective addition to the first 6-8 weeks of anti-tuberculosis treatment of TBM in patients with HIV, and investigate alternative management strategies in a subset of patients who develop drug induced liver injury (DILI) that will enable the safe continuation of rifampicin and isoniazid therapy. Methods: We will perform a parallel group, randomised (1:1), double blind, placebo-controlled multi-centre Phase III trial, comparing the effect of dexamethasone versus placebo on overall survival in HIV-infected patients with TBM, in addition to standard anti-tuberculosis and antiretroviral treatment. The trial will be set in two hospitals in Ho Chi Minh City, Vietnam, and two hospitals in Jakarta, Indonesia. The trial will enrol 520 HIV-infected adults. An ancillary study will perform a randomised comparison of three DILI management strategies with the aim of demonstrating which strategy results in the least interruption in rifampicin and isoniazid treatment. An identical ancillary study will also be performed in the linked randomised controlled trial of dexamethasone in HIV-uninfected adults with TBM stratified by LTA4H genotype (LAST ACT). Discussion: Whether corticosteroids confer a survival benefit in HIV-infected patients remains uncertain, and the current evidence base for using corticosteroids in this context is limited. Interruptions in anti-tuberculosis chemotherapy is a risk factor for death from TBM. Alternative management strategies in DILI may allow the safe continuation of rifampicin and isoniazid therapy.